Analisis Beban Kerja untuk Perencanaan Kebutuhan Karyawan pada Satuan Kerja Administrasi Perusahaan PT Timah (Persero) Tbk - Hutagalung, Renny; Gustomo, Aurik (The Indonesian Journal of Business Administration, 2013)
PT Timah (Persero) Tbk is a leading exporter of tin as well as the largest mining company in the world. As the industry competition is so tight, the company seeks to strengthen its business strategy of the company's long plan (2013-2017) that is doing the tin mining efficient and environmentally friendly in order to achieve profitability. One preparation to achieve the strategic HR planning that is ripe with a set amount of human resources that ideal. The final project is focused on employee workload measurement with observations using the method of work sampling observations made at intervals of several employees in the work unit Corporate Administration. Each employee was asked to fill in diary form sampling with principal activities, events and activities inhibitor leeway on work time. Workload information will be used to calculate the amount of the administrative needs of the employees of the Company. Workload information can also be used to predict future employee needs. Based on these calculations in this year, this data will be used to predict how much the number of employees needed for each job for next year. Number of employees in accordance with the workload will support the needs of employees in strategic planning unit in particular Corporate Administration and PT Timah (Persero) Tbk in general.Â Keywords : Planning Needs of Employees, Workload, Work Sampling.